The influence of antioxidant heat treatment on utilization of active oxygen forms during storage of cucumbers - Priss, Olesia; Danchenko, Olena; Yevlash, Viktoria; Zhukova, Valentina; Verkholantseva Valentуna; Stepanenko Dmytrо (Technology audit and production reserves, 2017)
The effect of heat treatment with antioxidants on the degree of chilling injury, the dynamics of malonic dialdehyde and enzymatic antioxidants in the storage of cucumbers is analyzed. It is shown that the combination of heat treatment and the antioxidant composition Chl+I+A makes it possible to avoid chilling injury until the end of storage. Cucumbers with heat treatment with antioxidants for the entire storage time demonstrate deviations from the background value of malonic dialdehyde by no more than 13.5 %, which reflects the stable functioning of the antioxidant system. Heat treatment with biologically active substances can slow the rate of decrease in activity of superoxide dismutase, which contributes to its activity at 60 % of the initial value after 28 days of storage. The use of this treatment induces catalase activity in cucumbers, which grows according to the degree of their cold tolerance. Heat treatment with antioxidants regulates the activity of peroxidase in cucumbers, which is evidence of the slowing down of aging processes.